2020
DOI: 10.1186/s13048-019-0599-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: LncRNA miR503HG interacts with miR-31-5p through multiple ways to regulate cancer cell invasion and migration in ovarian cancer

Abstract: The role of lncRNA miR503HG has been investigated in several types of cancer, but its functions in ovarian cancer (OC) is unclear. Analysis of TCGA dataset revealed a 50-fold lower expression level of miR503HG in OC tissues than that in non-tumor tissues, indicating the involvement of miR503HG in OC. Results in this study showed that miR503HG was downregulated in OC and predicted poor survival. Expression of miR503HG negatively correlated with the expression of miR-31-5p across OC and non-tumor tissues. RNA-RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The long intergenic non-coding RNA MIR503HG (miR-503 host gene) was shown to be downregulated in OvCa tissues. Patients with the lowest level of this lncRNA were characterized by poor survival [ 82 ] ( Table 1 ). In addition, MIR503HG suppressed OvCa cell invasion and migration.…”
Section: Suppressor Lncrnas As Cernas In Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The long intergenic non-coding RNA MIR503HG (miR-503 host gene) was shown to be downregulated in OvCa tissues. Patients with the lowest level of this lncRNA were characterized by poor survival [ 82 ] ( Table 1 ). In addition, MIR503HG suppressed OvCa cell invasion and migration.…”
Section: Suppressor Lncrnas As Cernas In Ovarian Cancermentioning
confidence: 99%
“…Interestingly, methylation-specific PCR showed that overexpression of MIR503HG led to an increased methylation level of the miR-31-5p gene. Therefore, MIR503HG may inhibit miR-31-5p in OvCa in two different ways: by sponging mature miR-31-5p and promoting the methylation of the miR-31-5p gene [ 82 ] ( Table 1 ).…”
Section: Suppressor Lncrnas As Cernas In Ovarian Cancermentioning
confidence: 99%
“…Surveying the function of lncRNAs globally (Figure 2b), 120 are considered as oncogenes, 114 confirmed and six putative; and 29 are considered as tumor suppressor genes, 25 confirmed and four putative. SPRY-IT1 [26], MEG3 [122,123], XIST [54,99] and TTN-AS1 [65,124] statuses remain unclear because the shreds of evidence collected are ambiguous. The experimental data about TC0101686, TC0100223, TC0901107, and TC1500845 show only that they are transcriptionally activated by estrogens.…”
Section: Lncrnas Implicated In Oc Development and Progressionmentioning
confidence: 99%
“…In addition to the studies mentioned above, lncRNA can also affect a miRNA in two ways. For instance, overexpression of LncRNA- miR503HG as a decreasing lncRNA in ovarian cancer (OC) cells may decrease the expression of miR-31-5p via sponging of miR-31-5p and increasing miR-31-5p gene's methylation [ 175 ]. Some miRNAs are involved in inhibition of lncRNA activities that may have a reciprocal interaction between lncRNAs and miRNAs; for example, lncRNA XIST and miR-132-3p repress each other in CRC cells [ 176 ].…”
Section: Introductionmentioning
confidence: 99%